2020
DOI: 10.5713/ajas.18.0984
|View full text |Cite
|
Sign up to set email alerts
|

L-arginine and N-carbamoylglutamic acid supplementation enhance young rabbit growth and immunity by regulating intestinal microbial community

Abstract: Objective: An experiment was conducted to determine the effects of L-arginine (L-Arg) and N-carbamoylglutamic acid (NCG) on the growth, metabolism, immunity and community of cecal bacterial flora of weanling and young rabbits. Methods: Eighteen normal-grade male weanling Japanese White rabbits (JWR) were selected and randomly divided into 6 groups with or without L-Arg and NCG supplementation. The whole feeding process was divided into weanling stage (day 37 to 65) and young stage (day 66 to 85). The effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…In this study, we found at the genus level, high red meat intake significantly increased the relative abundance of Bacteroides and Alistipes genera in colon, but reduced the abundance of Lachnospiraceae_NK4A136 group, Faecalibaculum, Blautia, and Dubosiella genera. Previous studies have shown that the genera of Bacteroides and Alistipes can affect amino acid transport, metabolism, energy production and transport, and inflammation (34)(35)(36). Bacteroides can secret metalloprotease toxin both in vivo and in vitro (37), which stimulate the cleavage of intercellular adhesion protein E-cadherin in colonic epithelial cells, resulting in increased colonic mucosal permeability and activating NF-kB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found at the genus level, high red meat intake significantly increased the relative abundance of Bacteroides and Alistipes genera in colon, but reduced the abundance of Lachnospiraceae_NK4A136 group, Faecalibaculum, Blautia, and Dubosiella genera. Previous studies have shown that the genera of Bacteroides and Alistipes can affect amino acid transport, metabolism, energy production and transport, and inflammation (34)(35)(36). Bacteroides can secret metalloprotease toxin both in vivo and in vitro (37), which stimulate the cleavage of intercellular adhesion protein E-cadherin in colonic epithelial cells, resulting in increased colonic mucosal permeability and activating NF-kB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The metagenome-assembled genomes of Mollicutes_RF9 group also have the CAZyme related with starch degradation, thus lower concentration of undigested starch flowing into the cecum might limit the growth of Mollicutes_RF9 (Ma et al, 2019) produce butyrate; in addition, genus norank_f_Lachnospiraceae, Shuttleworthia, and Ruminococcus_torques_group have been observed to be related to better performance (Torok et al, 2011;Lee et al, 2017;McCafferty et al, 2019a;Li et al, 2020). Genera (Hydrogenoanaerobacterium and Ruminococcaceae_V9D2013_group) from the phylum Firmicutes are also suggested to effectively produce butyrate (Fang et al, 2020;Ilaria et al, 2020;Sun et al, 2020). Genus unclassified_f_Ruminococcaceae, Anaerotruncus, Caproiciproducens, and Subdoligranulum (family Ruminococcaceae) are also known as short-chain fatty acid producers.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, the previous study indicated that the growth of Lactobacillus was dependent on the Arg to a great extent [33], and the lactic acid produced by Lactobacillus could be further used as substrate by butyrateproducing bacteria such as Ruminococcaceae [36]. In addition, Arg can modulate the metabolism of the Arg, serine and aspartate-family of amino acids in intestinal bacteria and decrease the utilization of most amino acids in mixed bacteria [37]. These may partly explain why Arg can stimulated probiotics and affected the microbiota.…”
Section: Discussionmentioning
confidence: 99%